Primary perforating dermatoses - current status - Klaudia Orłowska-Orlik; Anna Woźniacka; Jolanta D. Torzecka (Termedia Publishing House, 2016)
Primary perforating dermatoses (PPD) are a group of skin diseases rarely seen in everyday dermatological practice, which includes elastosis perforans serpiginosa, reactive perforating collagenosis, Kyrle disease and perforating folliculitis. These entities can be associated with chromosomal aberrations, chronic renal, cardiovascular or hepatic diseases. Unique histopathological findings in each PPD are useful in determination of the diagnosis. However, in other more frequently seen dermatoses of heterogeneous etiology, perforation of epidermis with material undergoing transepidermal elimination is also observed. Our article aims to present the most important recent information on epidemiology, pathogenesis, clinical findings, therapeutic options and differential diagnosis of primary perforating dermatoses.